Die forging forming method for high-strength, high-toughness and damage tolerance type titanium alloy cylindrical part

Through the die forging and forming method of high-strength and high-strength and damage tolerance type titanium alloy cylindrical parts, the problems of low processing efficiency and low material utilization rate of TC21 titanium alloy are solved, and the effect of reducing production costs and improving product performance is achieved.

CN119237632AActive Publication Date: 2025-01-03SHAANXI HEYE SPECIAL STEEL TOOL
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411487522.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-03
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The application of TC21 titanium alloy in the aviation industry is limited by its low processing technology efficiency, low material utilization rate and poor blanking quality, resulting in high production costs and unstable product performance.

Method used

The die forging forming method of high-strength and high-strength and damage tolerance titanium alloy cylindrical parts includes cutting processing, heating, primary forging, surface treatment, annealing and other steps. The β-phase transition temperature makes the titanium alloy forging easy to process and improves strength and toughness, and enhance material properties through annealing and surface treatment.

Benefits of technology

It reduces the weight of raw materials and forging fires, reduces production costs, and ensures stable product performance and quality, improving the strength, toughness and crack propagation resistance of titanium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237632A_ABST
    Figure CN119237632A_ABST
Patent Text Reader

Abstract

The invention discloses a die forging forming method for a high-strength, high-toughness and damage-tolerance type titanium alloy cylindrical part. The die forging forming method comprises the following steps of S1, raw material heating, S2, primary forging, S3, surface treatment, S4, secondary forging and S5, annealing. By means of the method, the raw material weight and the forging heating number can be reduced, the production cost is reduced, and meanwhile it can be guaranteed that all properties of the product are good, and the product quality stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal forging, and in particular to a die forging method for a high-strength, high-toughness and damage-tolerant titanium alloy cylindrical part. Background Art

[0002] TC21 titanium alloy has good strength, plasticity, fracture toughness, and crack growth rate matching, and is a titanium alloy with great application prospects. With the rapid development of the aviation industry towards lightweight structures, the emergence of new alloy materials is undoubtedly an important symbol of the development of advanced aircraft in my country. In order to accelerate the application of TC21 titanium alloy in the aviation industry, it is necessary to speed up the research on its related theories, form a mature processing technology, and develop its performance potential so that it can meet the performance requirements of the aviation industry for structural materials.

[0003] The original forging shape of the shell forging has a large single-sided machining allowance and the core is a solid structure, so its forging material utilization rate is low. During forging, the free forging billet needs to be stretched in two fires, which has low production efficiency and many surface billet defects. At the same time, it has the disadvantages of large product processing volume, long rough processing time and high processing cost. Therefore, it is necessary to optimize the forging processing method to improve the forging material utilization rate and improve the billet quality, so as to achieve the purpose of reducing costs and increasing efficiency. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part.

[0005] A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part comprises the following steps:

[0006] S1. Heating raw materials:

[0007] Take the titanium alloy forging material for cutting and then heat the titanium alloy forging material to (T β -50) ± 10℃, and then keep warm for 70 to 120 minutes to obtain the heated forging material; wherein, T β is the β phase transformation temperature of titanium alloy forging;

[0008] S2, one-time forging:

[0009] The heated forging material is placed in a forging die for forging at a hammering rate of 30 to 45 times / min, a forging time of 30 to 45 seconds, and a striking energy of 700 to 900 tons; then air-cooled to 25° C. to obtain a primary forging;

[0010] S3. Surface treatment:

[0011] After the forging is shot blasted, polished, and shot blasted again, the forging is kept at 120-150°C for 10-20 minutes, and then the forging is taken out and sprayed with glass lubricant. After the glass lubricant is dried, it is heated to a temperature of (T β -50)±10℃, then keep warm for 75~150min to obtain pre-forged parts;

[0012] S4, secondary forging;

[0013] The pre-forged piece is placed in a finished product mold for forging, wherein the striking energy is 1100-1250 tons during the forging process, and then air-cooled to 500-550° C., and a final forging piece is obtained after the forging is completed;

[0014] S5, Annealing:

[0015] The final forging is first annealed at 880-930° C. for 145-155 min, and then air-cooled to 300-450° C. to obtain a final forging after the primary annealing;

[0016] The final forging after the primary annealing is then subjected to secondary annealing at 500-550° C. for 235-245 minutes, and then air-cooled to 25° C. to obtain a formed part.

[0017] Description: The above method can reduce the weight of raw materials and the number of forging times, thereby reducing production costs, while ensuring that the various performances of the products are good and the stability of product quality; by heating the raw materials, the β phase transformation temperature of the titanium alloy forging material can be used to make the structure of the titanium alloy forging material in an easy-to-process state, and the strength and toughness of the titanium alloy forging material can be improved through one forging and two forgings. The surface treatment can protect the titanium alloy surface and prevent the occurrence of oxidation and other phenomena. Annealing can further improve the toughness and other properties.

[0018] Furthermore, the titanium alloy is TC21; T β It is 945~975℃.

[0019] Description: TC21 titanium alloy is a two-phase titanium alloy. The above-defined titanium alloy has high organizational strength and fracture toughness, strong resistance to crack propagation, and is an ideal organization for parts that serve for a long time at high temperatures.

[0020] Furthermore, in S2, when the heated titanium alloy is placed in a forging die for forging, the placement time is 0.1 to 15 seconds.

[0021] Note: By setting the above placement time, it is possible to prevent the titanium alloy surface from being oxidized, cracked, and other mineral-grabbing problems caused by too long a time.

[0022] Furthermore, in S1, the titanium alloy forging material is a shell forging; the diameter of the titanium alloy forging material after the cutting process is 55-95% of that before the cutting process, and the height of the titanium alloy forging material after the cutting process is 74-260% of that before the cutting process.

[0023] Note: The above-mentioned processing of the shell forging can reduce the processing cost in the prior art.

[0024] Furthermore, in S1, the method for cutting the titanium alloy forging material is: reducing the thickness of the titanium alloy forging material processing allowance, increasing the height of the upper punch of the titanium alloy forging material, increasing the length of the lower punch and boring.

[0025] Note: The above-mentioned cutting and processing method can ensure the quality stability of the titanium alloy used for shell forgings, and compared with the unprocessed shell forgings, its various performances are relatively close or even better.

[0026] Further, in S3, the method of performing shot blasting, grinding, and shot blasting again on the initial forging is:

[0027] The first shot blasting uses steel balls with a particle size of 2-2.5 mm and a shot blasting speed of 60-70 m / s; the grinding force used is 120-150 mesh and the grinding pressure is 5-15N; the second shot blasting uses steel balls with a particle size of 0.5-1.5 mm and a shot blasting speed of 30-50 m / s.

[0028] Note: The above surface treatment method makes the surface of the initial forging smoother and can introduce residual compressive stress on the alloy surface through two shot blasting processes, thereby improving the fatigue strength and stress corrosion cracking resistance of the material.

[0029] Furthermore, the thickness of the sprayed glass lubricant is 1 to 3 mm, and the glass lubricant is a modified borosilicate glass lubricant.

[0030] Note: By setting the above-mentioned spraying glass lubricant, the surface of the initial forging can be better protected, the service life of the forging can be extended, and the high temperature resistance of the forging can be improved.

[0031] Furthermore, the modified borosilicate glass lubricant is prepared by the following steps:

[0032] Borax, sodium silicate, magnesium oxide and zinc oxide are taken in a mass ratio of 2-3:1-2:0.05:0.03, put into a ball mill, and ball mill at a rate of 200r / min for 30-40min, and then put into a high-temperature furnace and melt at a temperature of 1300-1400℃ for 2-4h; the molten glass is rapidly cooled, quenched with water, and ground to obtain glass powder;

[0033] A silane coupling agent accounting for 15 to 20% of the mass of the glass powder is added to the glass powder and continuously stirred to obtain a mixture, the mixture is mixed with polytetrafluoroethylene powder at a mass ratio of 10:1 to 2, and then dried until the moisture content is less than 0.1% to obtain a modified borosilicate glass lubricant.

[0034] Description: The modified borosilicate glass lubricant obtained by the above method has good thermal stability and chemical stability, and can improve the lubrication performance and the bonding force with the titanium alloy surface.

[0035] Furthermore, during the primary annealing, under normal pressure and nitrogen atmosphere, the final forging is first heated to 880-930° C. at a heating rate of 5-7° C. / min, then kept at a constant temperature for 145-155 min, and then cooled to 300-450° C. at a cooling rate of 8-10° C. / min;

[0036] During the secondary annealing process, the final forging after the primary annealing is first heated to 500-550°C at a heating rate of 8-10°C / min under a pressure of 0.22-0.30 MPa and a nitrogen atmosphere, then kept at a constant temperature for 235-245 minutes, and then cooled to 25°C at a cooling rate of 4-6°C / min.

[0037] Note: The above method can relieve the internal stress generated in the forging process through two annealings, preventing the material from cracking or deforming in subsequent processing. At the same time, it can refine the grains, thereby improving the metal's microstructure and ductility, thereby improving the overall performance of the material.

[0038] Furthermore, during the constant temperature standing process of the primary annealing, a magnetic field with a magnetic field strength of 20 to 50 Oe is applied, and the magnetic field strength decreases with the constant temperature standing time, and the reduction rate is 0.1 Oe / min. When the constant temperature standing is completed and the cooling begins, the magnetic field is turned off, and nitrogen is filled to a pressure of 0.18 to 0.20 MPa, and after the cooling is completed, the pressure is adjusted to normal pressure;

[0039] During the constant temperature standing process of the secondary annealing, a magnetic field with a magnetic field strength of 20 to 50 Oe is applied, and the magnetic field strength first increases and then decreases with the constant temperature standing time. In the first 100 minutes of the constant temperature standing, the magnetic field strength increases at a rate of 0.15 Oe / min, and in the subsequent constant temperature standing time, the magnetic field strength decreases at a rate of 0.1 Oe / min. After the constant temperature standing is completed, the magnetic field is turned off, the pressure is adjusted to normal pressure, and then the temperature is lowered.

[0040] Note: The above-mentioned conditions during the constant temperature static process can enhance the annealing effect, and have a good improvement effect on the organizational structure of the titanium alloy of this scheme, so that it has high-strength, high-toughness damage tolerance characteristics.

[0041] The beneficial effects of the present invention are:

[0042] The method of the present invention can reduce the weight of raw materials and the number of forgings, thereby reducing production costs, and can also ensure that the various properties of the product are good and the stability of product quality; by heating the raw materials, the β phase transformation temperature of the titanium alloy forging material can be used to make the structure of the titanium alloy forging material in an easy-to-process state, and the strength and toughness of the titanium alloy forging material can be improved through one forging and two forgings. The surface treatment can protect the surface of the titanium alloy to prevent the occurrence of oxidation and other phenomena, and annealing can further improve the toughness and other properties. TC21 titanium alloy belongs to a two-phase titanium alloy, and the typical microstructures mainly include equiaxed structure, dual-state structure, basket structure and Widmanstatten structure. Among them, the basket structure is a basket-like structure woven by the transformation of the α phase. This structure has high strength and fracture toughness, strong crack propagation resistance, and is an ideal structure for parts in long-term high-temperature service. The surface treatment method makes the surface of the initial forging smoother and can introduce residual compressive stress on the alloy surface through two shot blasting methods, which can improve the fatigue strength and stress corrosion cracking resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a comparison diagram before and after cutting processing of Example 1 of the present invention;

[0044] Figure 2 is a comparison diagram before and after cutting processing of Example 17 of the present invention;

[0045] Figure 3 It is a comparison diagram before and after cutting processing of Example 18 of the present invention. DETAILED DESCRIPTION

[0046] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0047] Embodiment 1: A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part, comprising the following steps:

[0048] S1. Heating raw materials:

[0049] Taking a titanium alloy forging material for cutting processing, then heating the titanium alloy forging material to 925° C. and then keeping the temperature for 100 minutes; obtaining a heated forging material; the titanium alloy forging material is a shell forging, the forging specification is: Φ85±1×215±1mm, weight: 5.51Kg, quota: 5.63Kg; the diameter of the titanium alloy forging material after cutting processing is 70% of that before cutting processing, and the height of the titanium alloy forging material after cutting processing is 120% of that before cutting processing;

[0050] like Figure 1 As shown, in S1, the method for cutting the titanium alloy forging material is: reducing the thickness of the titanium alloy forging material processing allowance, increasing the height of the upper punch of the titanium alloy forging material, increasing the length of the lower punch and digging a hole;

[0051] S2, one-time forging:

[0052] The heated forging material is placed in a forging die for forging, the forging hammer rate is 40 times / min, the forging time is: 30s, and the striking energy is 800 tons; then air-cooled to 25°C to obtain a preliminary forging; in S2, when the heated titanium alloy is placed in a forging die for forging, the placement time is 5s;

[0053] S3. Surface treatment:

[0054] The forging is subjected to shot blasting, grinding, and shot blasting again, and then the forging is kept at 140° C. for 15 minutes, and then the forging is taken out and sprayed with glass lubricant, and after the glass lubricant is dried, it is heated to a temperature of 925° C. for the forging, and then kept at this temperature for 100 minutes to obtain a pre-forging;

[0055] In S3, the method of performing shot blasting, grinding, and shot blasting again on the initial forging is:

[0056] The first shot blasting uses steel balls with a particle size of 2.1 mm and a shot blasting speed of 65 m / s; the grinding force used is 130 mesh and the grinding pressure is 10 N; the second shot blasting uses steel balls with a particle size of 1 mm and a shot blasting speed of 40 m / s;

[0057] The thickness of the sprayed glass lubricant is 2 mm, and the glass lubricant adopts modified borosilicate glass lubricant.

[0058] The modified borosilicate glass lubricant is prepared by the following steps:

[0059] Borax, sodium silicate, magnesium oxide and zinc oxide were taken in a mass ratio of 2.5:1.5:0.05:0.03, put into a ball mill, and ball milled at a rate of 200r / min for 35min, and then put into a high-temperature furnace and melted at a temperature of 1350℃ for 3h; the molten glass was rapidly cooled, quenched with water and ground to obtain glass powder;

[0060] A silane coupling agent accounting for 18% of the mass of the glass powder is added to the glass powder and stirred continuously to obtain a mixture, the mixture is mixed with polytetrafluoroethylene powder at a mass ratio of 10:1.5, and then dried until the moisture content is less than 0.1% to obtain a modified borosilicate glass lubricant.

[0061] S4, secondary forging;

[0062] The pre-forged part is placed in a finished product mold for forging. During the forging process, the striking energy is 1200 tons, and then air-cooled to 525° C. After the forging is completed, a final forging is obtained;

[0063] S5, Annealing:

[0064] The final forging is first annealed at 900° C. for 150 min, and then air-cooled to 400° C. to obtain a final forging after the first annealing;

[0065] The final forging after the primary annealing is then subjected to secondary annealing at 510° C. for 240 min, and then air-cooled to 25° C. to obtain a formed part;

[0066] During the primary annealing, under normal pressure and nitrogen atmosphere, the final forging is first heated to 900° C. at a heating rate of 6° C. / min, then kept at a constant temperature for 150 min, and then cooled to 400° C. at a cooling rate of 9° C. / min;

[0067] During the secondary annealing, the final forging after the primary annealing is first heated to 510°C at a heating rate of 9°C / min under a nitrogen atmosphere at a pressure of 0.25 MPa, then kept at a constant temperature for 240 minutes, and then cooled to 25°C at a cooling rate of 5°C / min.

[0068] Example 2: This example is different from Example 1 in that the parameters of heating the raw materials in S1 are different. The titanium alloy forging material is cut and processed, and then the titanium alloy forging material is heated to 915°C and kept warm for 70 minutes to obtain the heated forging material; wherein, T βis the β phase transformation temperature of the titanium alloy forging material; the titanium alloy is TC21; the titanium alloy forging material is a shell forging; the diameter of the titanium alloy forging material after cutting is 55% of that before cutting, and the height of the titanium alloy forging material after cutting is 260% of that before cutting.

[0069] Example 3: This example is different from Example 1 in that the parameters of heating the raw materials in S1 are different. The titanium alloy forging material is cut and processed, and then the titanium alloy forging material is heated to 935°C and kept warm for 120 minutes to obtain the heated forging material; wherein, T β is the β phase transformation temperature of the titanium alloy forging material; the titanium alloy is TC21; the titanium alloy forging material is a shell forging; the diameter of the titanium alloy forging material after cutting is 95% of that before cutting, and the height of the titanium alloy forging material after cutting is 74% of that before cutting.

[0070] Example 4: This example is different from Example 1 in that the parameters of the first forging in S2 are different. The heated forging material is placed in a forging die for forging, the hammering rate is 30 times / min, the forging time is 45 seconds, and the striking energy is 700 tons; then it is air-cooled to 25°C to obtain a preliminary forging; in S2, when the heated titanium alloy is placed in a forging die for forging, the placement time is 15 seconds.

[0071] Example 5: This example is different from Example 1 in that the parameters of the first forging in S2 are different. The heated forging material is placed in a forging die for forging, the hammering rate is 45 times / min, the forging time is 30 seconds, and the striking energy is 900 tons; then it is air-cooled to 25°C to obtain a preliminary forging; in S2, when the heated titanium alloy is placed in a forging die for forging, the placement time is 0.1 seconds.

[0072] Example 6: This example is different from Example 1 in that the parameters of the S3 surface treatment are different. After the rough forging is subjected to shot blasting, grinding, and shot blasting again, the rough forging is kept at 120°C for 20 minutes, and then the rough forging is taken out and sprayed with glass lubricant. After the glass lubricant is dried, it is heated to a temperature of 925°C for the rough forging, and then kept warm for 75 minutes to obtain a pre-forging;

[0073] The method of performing shot blasting, grinding and shot blasting again on the initial forging is: the first shot blasting uses steel balls with a particle size of 2.5 mm and a shot blasting speed of 70 m / s; the grinding force used is 150 mesh and the grinding pressure is 15N; the second shot blasting uses steel balls with a particle size of 1.5 mm and a shot blasting speed of 30 m / s.

[0074] Example 7: This example is different from Example 1 in that the parameters of the S3 surface treatment are different. After the rough forging is subjected to shot blasting, grinding, and shot blasting again, the rough forging is kept at 150° C. for 10 minutes, and then the rough forging is taken out and sprayed with glass lubricant. After the glass lubricant is dried, it is heated to a temperature of 925° C. for the rough forging, and then kept warm for 150 minutes to obtain a pre-forging;

[0075] The method of performing shot blasting, grinding and shot blasting again on the initial forging is: the first shot blasting uses steel balls with a particle size of 2 mm and a shot blasting speed of 60 m / s; the grinding force used is 120 mesh and the grinding pressure is 5N; the second shot blasting uses steel balls with a particle size of 0.5 mm and a shot blasting speed of 50 m / s.

[0076] Example 8: This example is different from Example 1 in that the preparation parameters of the modified borosilicate glass lubricant are different. Borax, sodium silicate, magnesium oxide and zinc oxide are taken in a mass ratio of 3:1:0.05:0.03, put into a ball mill, and ball milled at a rate of 200 r / min for 40 minutes, and then put into a high-temperature furnace and melted at a temperature of 1300°C for 4 hours; the molten glass is rapidly cooled, quenched with water, and ground to obtain glass powder;

[0077] A silane coupling agent accounting for 15% of the mass of the glass powder is added to the glass powder and stirred continuously to obtain a mixture, the mixture is mixed with polytetrafluoroethylene powder at a mass ratio of 10:1, and then dried until the moisture content is less than 0.1% to obtain a modified borosilicate glass lubricant.

[0078] Example 9: This example is different from Example 1 in that the preparation parameters of the modified borosilicate glass lubricant are different. Borax, sodium silicate, magnesium oxide and zinc oxide are taken in a mass ratio of 2:2:0.05:0.03, put into a ball mill, ball milled at a rate of 200 r / min for 30 minutes, and then put into a high-temperature furnace and melted at a temperature of 1400°C for 2 hours; the molten glass is rapidly cooled, quenched with water and ground to obtain glass powder;

[0079] A silane coupling agent accounting for 20% of the mass of the glass powder is added to the glass powder and stirred continuously to obtain a mixture, the mixture is mixed with polytetrafluoroethylene powder at a mass ratio of 10:2, and then dried until the moisture content is less than 0.1% to obtain a modified borosilicate glass lubricant.

[0080] Example 10: This example is different from Example 1 in that the parameters of the S4 secondary forging are different. The pre-forged part is placed in a finished product mold for forging. During the forging process, the striking energy is 1100 tons, and then air-cooled to 500°C. After the forging is completed, the final forging is obtained.

[0081] Example 11: This example is different from Example 1 in that the parameters of the S4 secondary forging are different. The pre-forged part is placed in a finished product mold for forging. During the forging process, the striking energy is 1250 tons and then air-cooled to 550°C. After the forging is completed, the final forging is obtained.

[0082] Example 12: This example is different from Example 1 in that the parameters of S5 annealing are different. The final forging is first annealed at 880°C for 155 minutes, and then air-cooled to 300°C to obtain a final forging after the first annealing; the final forging after the first annealing is then subjected to a second annealing at 550°C for 235 minutes, and then air-cooled to 25°C to obtain a formed part.

[0083] During the primary annealing, under normal pressure and nitrogen atmosphere, the final forging is first heated to 880° C. at a heating rate of 5° C. / min, then kept at a constant temperature for 155 minutes, and then cooled to 450° C. at a cooling rate of 10° C. / min;

[0084] During the secondary annealing, the final forging after the primary annealing is first heated to 550°C at a heating rate of 8°C / min under a pressure of 0.22 MPa and a nitrogen atmosphere, then kept at a constant temperature for 245 minutes, and then cooled to 25°C at a cooling rate of 4°C / min.

[0085] Example 13: This example is different from Example 1 in that the parameters of S5 annealing are different. The final forging is first annealed at 930°C for 145 minutes, and then air-cooled to 450°C to obtain a final forging after the first annealing; the final forging after the first annealing is then subjected to a second annealing at 550°C for 235 minutes, and then air-cooled to 25°C to obtain a formed part.

[0086] During the primary annealing, under normal pressure and nitrogen atmosphere, the final forging is first heated to 930° C. at a heating rate of 7° C. / min, then kept at a constant temperature for 145 min, and then cooled to 300° C. at a cooling rate of 8° C. / min;

[0087] During the secondary annealing, the final forging after the primary annealing is first heated to 500°C at a heating rate of 10°C / min under a pressure of 0.30 MPa and a nitrogen atmosphere, then kept at a constant temperature for 235 minutes, and then cooled to 25°C at a cooling rate of 6°C / min.

[0088] Example 14: This example is different from Example 1 in that, during the constant temperature standing process of the primary annealing, a magnetic field with a magnetic field strength of 40 Oe is applied, and the magnetic field strength decreases with the constant temperature standing time, and the reduction rate is 0.1 Oe / min. When the constant temperature standing is completed and the cooling begins, the magnetic field is turned off, and nitrogen is filled to a pressure of 0.19 MPa. After the cooling is completed, the pressure is adjusted to normal pressure;

[0089] During the constant temperature standing process of the secondary annealing, a magnetic field with a magnetic field strength of 45 Oe is applied, and the magnetic field strength first increases and then decreases with the constant temperature standing time. In the first 100 minutes of the constant temperature standing, the magnetic field strength increases at a rate of 0.15 Oe / min, and in the subsequent constant temperature standing time, the magnetic field strength decreases at a rate of 0.1 Oe / min. After the constant temperature standing is completed, the magnetic field is turned off, the pressure is adjusted to normal pressure, and then the temperature is lowered.

[0090] Example 15: This example is different from Example 14 in that the processing parameters of the primary annealing and the secondary annealing are different. During the primary annealing, a magnetic field with a magnetic field strength of 50 Oe is applied, and the magnetic field strength decreases with the constant temperature standing time, and the reduction rate is 0.1 Oe / min. When the constant temperature standing is completed and the cooling begins, the magnetic field is turned off and nitrogen is filled to a pressure of 0.20 MPa. After the cooling is completed, the pressure is adjusted to normal pressure.

[0091] During the constant temperature standing process of the secondary annealing, a magnetic field with a magnetic field strength of 20 Oe is applied, and the magnetic field strength first increases and then decreases with the constant temperature standing time. In the first 100 minutes of the constant temperature standing, the magnetic field strength increases at a rate of 0.15 Oe / min, and in the subsequent constant temperature standing time, the magnetic field strength decreases at a rate of 0.1 Oe / min. After the constant temperature standing is completed, the magnetic field is turned off, the pressure is adjusted to normal pressure, and then the temperature is lowered.

[0092] Example 16: This example is different from Example 14 in that the processing parameters of the primary annealing and the secondary annealing are different. During the primary annealing, a magnetic field with a magnetic field strength of 20 Oe is applied, and the magnetic field strength decreases with the constant temperature standing time, and the reduction rate is 0.1 Oe / min. When the constant temperature standing is completed and the cooling begins, the magnetic field is turned off and nitrogen is filled to a pressure of 0.18 MPa. After the cooling is completed, the pressure is adjusted to normal pressure.

[0093] During the constant temperature standing process of the secondary annealing, a magnetic field with a magnetic field strength of 50 Oe is applied, and the magnetic field strength first increases and then decreases with the constant temperature standing time. In the first 100 minutes of the constant temperature standing, the magnetic field strength increases at a rate of 0.15 Oe / min, and in the subsequent constant temperature standing time, the magnetic field strength decreases at a rate of 0.1 Oe / min. After the constant temperature standing is completed, the magnetic field is turned off, the pressure is adjusted to normal pressure, and then the temperature is lowered.

[0094] Embodiment 17: This embodiment differs from Embodiment 1 in that the shape of the shell forging is different, such as Figure 2 As shown, the method for cutting the titanium alloy forging material described in S1 is specifically as follows: machining allowance: adjusting the single-sided allowance of the outer diameter of the forging from 3.0mm to 1.0mm; adjusting the single-sided machining allowance of the inner diameter from 11.0mm to 2.0mm; the single-sided machining amount in the height direction remains unchanged; forging shape: adjusting the height of the upper punch of the original forging from 41mm to 120mm, and adding a 35mm punch to the lower die, thereby reducing the material used in the core of the forging; forging blanking before cutting: Φ90×295, quota: 8.6Kg; forging blanking after cutting: Φ85×220, quota: 5.7Kg; material reduction ≈2.9Kg; rough machining: the original forging core is solid ≈144mm, and the optimized forging has a middle skin ≈30mm. When rough machining holes, the machining time can be greatly reduced; at the same time, the outer diameter / inner diameter machining allowance of the forging is reduced, which also reduces the rough machining time to a certain extent.

[0095] Embodiment 18: This embodiment differs from Embodiment 1 in that the shape of the shell forging is different, such as Figure 3 As shown, the method for cutting the titanium alloy forging material described in S1 is specifically as follows: machining allowance: adjusting the single-side allowance of the outer diameter of the forging from 3.0 mm to 1.0 mm; adjusting the single-side machining allowance of the inner diameter of the forging from 10.0 mm to 2.0 mm; forging shape: adjusting the upper punch height of the original forging from 24 mm to 101 mm, and adding a 35 mm punch to the lower die, thereby reducing the material used in the core of the forging; the blanking of the forging before cutting: Φ154×130, quota: 11.3 kg; the blanking of the forging before and after cutting: Φ85×335, quota: 8.6 kg; material reduction ≈ 2.7 kg;

[0096] Forging times: The original forging scheme required two fires to lengthen the free forging billet, and the single-piece operation time was ≈6 minutes. After optimization, the free forging billet only needs one fire to complete, and the single-piece operation time is ≈1.5 minutes. The number of forging fires is reduced and the operation time is shortened; Rough machining: The original forging core is solid ≈227mm, and the optimized forging with skin in the middle is ≈111mm. When rough machining holes, the processing time can be greatly reduced.

[0097] Experimental Example: Multiple performance tests were conducted on the samples obtained from Examples 1 to 16, and the test results are as follows:

[0098] 1. Explore the effects of different treatment methods on the performance of formed parts;

[0099] Comparative Example 1: The difference from Example 1 is that no cutting process is performed and forging is directly performed.

[0100] Comparative Example 2: The difference from Example 1 is that no grinding and re-shot blasting were performed, and only shot blasting was performed once.

[0101] Comparative Example 3: The difference from Example 1 is that a commercially available borosilicate glass lubricant is used.

[0102] Comparative Example 4: The difference from Example 1 is that the heating rate and cooling rate of the primary annealing and the secondary annealing are the same, both of which are 9°C / min.

[0103] 1. First, 100 shell forgings were produced according to the methods of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, and then the qualified rates of the finished products obtained by each method were statistically analyzed. The statistical results show that the surface of Example 1 is relatively normal, and no cracks or the like are found; correspondingly, some shell forgings of Comparative Examples 2 and 3 have cracks.

[0104] 2. Comparison of performance tests of Example 1, Example 2, Example 3, Example 14, and Comparative Examples 1 to 4 is shown in Table 1;

[0105] Table 1 Performance test results of finished products obtained by forging under different treatment methods

[0106]

[0107] Combination Figure 1 As can be seen from Table 1, by comparing Example 1 with Comparative Example 1, it can be seen that the performance of the finished product in Example 1 is relatively close to that in Comparative Example 1. Compared with Comparative Example 1, Example 1 reduces the processing allowance, but its various performances are not reduced. In other words, compared with Comparative Example 1, the processing method of Example 1 can reduce the production cost.

[0108] By comparing Example 1 with Comparative Example 2, it can be seen that compared with the setting of no grinding and secondary shot blasting in Comparative Example 2, the surface performance and fatigue resistance of Example 1 can be improved after the treatment of secondary shot blasting. The surface performance is mainly reflected in surface defects such as cracks, pinching, folding, pits, etc.

[0109] By comparing Example 1 with Comparative Example 3, it can be found that the glass lubricant prepared in Example 1 is more preferred, which can better protect the titanium alloy and prevent the influence of oxidation on the strength and toughness of the alloy, thereby improving the corresponding mechanical properties. Although the glass lubricant in Comparative Example 3 can play a protective role, its stability is slightly worse than that of the glass lubricant in Example 1.

[0110] By comparing Example 1 with Comparative Example 4, it can be seen that the different settings in Example 1 can further improve the various properties of the titanium alloy. Among them, the two annealings in Example 1 relieve the internal stress generated in the forging process, preventing the material from cracking or deforming in subsequent processing. At the same time, it can refine the grains, thereby improving the metal's microstructure and ductility, thereby improving the overall performance of the material.

[0111] By comparing Example 1, Example 2 and Example 3, it can be found that the components of Example 1 are more preferred.

[0112] By comparing Example 1 and Example 14, it can be found that Example 14 has a better microstructure and a smaller crystal grain size, which helps to improve its elongation at break.

[0113] 2. Explore the impact of different parameters on;

[0114] Example 1 and Examples 4-13 were compared, as shown in Table 2;

[0115] Table 2 Performance test results of finished products obtained by forging under different parameter settings

[0116] parameter Tensile strength MPa Yield strength MPa Example 1 1350 1180 Example 4 1320 1146 Example 5 1322 1154 Example 6 1331 1137 Example 7 1335 1158 Example 8 1327 1167 Example 9 1325 1165 Example 10 1311 1147 Embodiment 11 1326 1149 Example 12 1315 1170 Example 13 1314 1165

[0117] As can be seen from Table 2, by comparing Example 1, Example 4 and Example 5, it can be found that the parameters of the first forging of Example 1 are more preferred, and the reason may be that through the first forging, the titanium alloy surface can be protected by surface treatment to prevent the occurrence of oxidation and the like, thereby improving the strength and toughness of the titanium alloy forging material; by comparing Example 1, Example 6 and Example 7, it can be found that the parameters of the surface treatment of Example 1 are more preferred; by comparing Example 1, Example 8 and Example 9, it can be seen that the preparation parameters of the modified borosilicate glass lubricant of Example 1 are more preferred, and the reason may be that under the parameters of Example 1, the anti-oxidation properties of the modified borosilicate glass lubricant obtained are better, and thus the quality of the finished product obtained in Example 1 is better; by comparing Example 1, Example 10 and Example 11, it can be seen that the setting of the secondary forging parameters of Example 1 is more preferred, and under this parameter, the internal structure of the finished product is more uniform; by comparing Example 1, Example 12 and Example 13, it can be found that the annealing parameters of Example 1 are more preferred.

Claims

1. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part, characterized in that: The following steps are involved: S1. Heating raw materials: Take the titanium alloy forging material for cutting and then heat the titanium alloy forging material to (T β -50) ± 10℃, and then keep warm for 70 to 120 minutes to obtain the heated forging material; wherein, T β is the β phase transformation temperature of titanium alloy forging; S2, one-time forging: The heated forging material is placed in a forging die for forging at a hammering rate of 30 to 45 times / min, a forging time of 30 to 45 seconds, and a striking energy of 700 to 900 tons; then air-cooled to 25° C. to obtain a primary forging; S3. Surface treatment: After the forging is shot blasted, polished, and shot blasted again, the forging is kept at 120-150°C for 10-20 minutes, and then the forging is taken out and sprayed with glass lubricant. After the glass lubricant is dried, it is heated to a temperature of (T β -50)±10℃, then keep warm for 75~150min to obtain pre-forged parts; S4, secondary forging; The pre-forged piece is placed in a finished product mold for forging, wherein the striking energy is 1100-1250 tons during the forging process, and then air-cooled to 500-550° C., and a final forging piece is obtained after the forging is completed; S5, Annealing: The final forging is first annealed at 880-930° C. for 145-155 min, and then air-cooled to 300-450° C. to obtain a final forging after the primary annealing; The final forging after the primary annealing is then subjected to secondary annealing at 500-550° C. for 235-245 minutes, and then air-cooled to 25° C. to obtain a formed part.

2. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 1, characterized in that: The titanium alloy is TC21; β It is 945~975℃.

3. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 1, characterized in that: In S2, when the heated titanium alloy is placed in a forging die for forging, the placement time is 0.1 to 15 seconds.

4. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 1, characterized in that: In S1, the titanium alloy forging material is a shell forging; the diameter of the titanium alloy forging material after the cutting process is 55-95% of that before the cutting process, and the height of the titanium alloy forging material after the cutting process is 74-260% of that before the cutting process.

5. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 4, characterized in that: In S1, the method for cutting the titanium alloy forging material is: reducing the thickness of the titanium alloy forging material processing allowance, increasing the height of the upper punch of the titanium alloy forging material, increasing the length of the lower punch and boring.

6. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 1, characterized in that: In S3, the method of performing shot blasting, grinding, and shot blasting again on the initial forging is: The first shot blasting uses steel balls with a particle size of 2-2.5 mm and a shot blasting speed of 60-70 m / s; the grinding force used is 120-150 mesh and the grinding pressure is 5-15N; the second shot blasting uses steel balls with a particle size of 0.5-1.5 mm and a shot blasting speed of 30-50 m / s.

7. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 1, characterized in that: The thickness of the sprayed glass lubricant is 1-3 mm, and the glass lubricant is a modified borosilicate glass lubricant.

8. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 1, characterized in that: During the primary annealing, under normal pressure and nitrogen atmosphere, the final forging is first heated to 880-930° C. at a heating rate of 5-7° C. / min, then kept at a constant temperature for 145-155 min, and then cooled to 300-450° C. at a cooling rate of 8-10° C. / min; During the secondary annealing process, the final forging after the primary annealing is first heated to 500-550°C at a heating rate of 8-10°C / min under a pressure of 0.22-0.30 MPa and a nitrogen atmosphere, then kept at a constant temperature for 235-245 minutes, and then cooled to 25°C at a cooling rate of 4-6°C / min.

9. A die forging method for a high-strength, high-toughness, damage-tolerant titanium alloy cylindrical part as claimed in claim 8, characterized in that: During the constant temperature standing process of the primary annealing, a magnetic field with a magnetic field strength of 20 to 50 Oe is applied, and the magnetic field strength decreases with the constant temperature standing time, and the reduction rate is 0.1 Oe / min. When the constant temperature standing is completed and the cooling begins, the magnetic field is turned off, and nitrogen is filled to a pressure of 0.18 to 0.20 MPa, and the pressure is adjusted to normal pressure after the cooling is completed; During the constant temperature standing process of the secondary annealing, a magnetic field with a magnetic field strength of 20 to 50 Oe is applied, and the magnetic field strength first increases and then decreases with the constant temperature standing time. In the first 100 minutes of the constant temperature standing, the magnetic field strength increases at a rate of 0.15 Oe / min, and in the subsequent constant temperature standing time, the magnetic field strength decreases at a rate of 0.1 Oe / min. After the constant temperature standing is completed, the magnetic field is turned off, the pressure is adjusted to normal pressure, and then the temperature is lowered.

Citation Information

Patent Citations

  • Upsetting and extruding precision die-forging forming method for large titanium alloy deep tube parts

    CN101693279A

  • Near isothermal forging method for whole titanium alloy disc shaft forgeable piece

    CN101758159A

  • Method for preparing Cu-Fe alloy under action of magnetic field

    CN102031399A

  • Forging process method for sblank of automobile transmission flange forgings

    CN102172768A

  • Forging process for lock case

    CN105344900A